If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -2(2x + -4) = 9x + 9 Reorder the terms: 14x + -2(-4 + 2x) = 9x + 9 14x + (-4 * -2 + 2x * -2) = 9x + 9 14x + (8 + -4x) = 9x + 9 Reorder the terms: 8 + 14x + -4x = 9x + 9 Combine like terms: 14x + -4x = 10x 8 + 10x = 9x + 9 Reorder the terms: 8 + 10x = 9 + 9x Solving 8 + 10x = 9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 8 + 10x + -9x = 9 + 9x + -9x Combine like terms: 10x + -9x = 1x 8 + 1x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 8 + 1x = 9 + 0 8 + 1x = 9 Add '-8' to each side of the equation. 8 + -8 + 1x = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 9 + -8 1x = 9 + -8 Combine like terms: 9 + -8 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 |